Health access inequalities in Chile: a multifactorial study based on the 2013 CASEN Survey - Jiménez, Simi; Barriga, Omar; Salazar, Alide (Revista Chilena de Salud Pública, 2018)
Objective: The purpose of this research is to describe the health access inequities among the Chilean Health Services and to identify structural determinants of inequity at a territorial level, through multifactorial analyses. Method: A quantitative descriptive study was conducted, using an exploratory statistic strategy application based on Multiple Correspondence Analyses (MCA) with the 2013 CASEN Survey data. Health Services were the unit of analysis, and inequities were determined by using the indicators of health system access and health service offerings that are included in the multidimensional poverty measure, which was incorporated in this version of the CASEN survey. Income quintile and an income poverty measure were used as indicators of social inequity. Results: While there are significant statistical differences among the country’s Health Services, in terms of the demographic and sociocultural characteristics of the populations they cover, there is little clarity as to the foundations of structural inequity determinants, which differs from what was initially hypothesized. This finding was confirmed through Multiple Correspondence Analyses. Conclusions: It is not possible to establish the existence of health access inequities, in terms of Chilean Health Services, with the 2013 CASEN Survey data.